Review: Non-Invasive Continuous Blood Glucose Measurement Techniques - Asmat Nawaz; Per Øhlckers; Steinar Sælid; Morten Jacobsen; M. Nadeem Akram (Journal of Bioinformatics And Diabetes, 2016)
Diabetes is a metabolic disorder that results in human body due to insulin deficiency, insulin resistance or both. In the management of diabetes, glucose monitoring technology has been used for the last three decades. The aim of this review article is to describe concise and organized information about different techniques of non-invasive continuous blood glucose monitoring. Many research groups have been working to develop wearable sensors for continuous blood glucose monitoring, but at present, there are to our knowledge no commercially successful non-invasive glucose monitors on the market. To achieve an acceptable sensor system, a glucose sensor should have accuracy better than 15mg/dl (0.8 mmol/l). In future development, continuous glucose sensor systems may become predictable, selective, reliable and acceptable for patient use.
Keywords: non-invasive